Study on mechanical properties and self-sensing properties of sprayed high-performance concrete containing glass aggregate - Wang, Jing; Wang, Tianren; Zhang, Yunlong; Qian, Xuesong (Frontiers in Materials, 2024)
Using glass sand as a substitute for sand in high-performance concrete not only conserves resources but also helps protect the environment. This study replaced manufactured sand with glass sand and added carbon fiber to prepare high-performance shotcrete. Its mechanical and self-sensing properties were then tested separately. The findings suggest that with an increase in glass sand content, the compressive strength of high-performance shotcrete initially rises and subsequently declines. When the replacement ratio of glass sand is 75%, the compressive strength exhibits its maximum value, whereas an increase in the glass sand content leads to a reduction in both splitting tensile strength and flexural strength. Although increasing carbon fiber content does not significantly contribute to compressive strength, it significantly improves flexural strength and splitting tensile strength. In addition, when testing the self-sensing performance of the material, it was found that its self-sensing performance increased significantly with increasing carbon fiber content but decreased with increasing glass sand content. Finally, an Ansys APDL simulation using the relevant parameters of the optimal group of mechanical properties was performed to model a tunnel and verify its feasibility and validity. This study provides a theoretical and practical reference for future engineering applications.